The effect of load cycling on microleakage of low shrinkage methacrylate base composite compared with silorane base composite and SEM evaluation of marginal integrity - Hamid Kermanshah; Esmaiel Yasini; Razieh Hoseinifar (Tehran University of Medical Sciences, 2013)
Background and Aims: Marginal seal in class V cavity and determination of the best restorative material in reducing microleakage is of great concern in operative dentistry. The aim of this study was to evaluate the effect of load cycling on the microleakage of low shrinkage composites compared with methacrylate-based composites with low shirinkage rate in class V cavity preparation. Marginal integrity of these materials was assessed using scanning electron microscope (SEM). Materials and Methods: In this in vitro study, class V cavity preparations were made on the buccal and lingual surfaces of 48 human premolars and molars (96 cavities). The specimens were divided into four groups each containing 12 teeth (24 cavities): group 1 (Kalore-GC+ G-Bond) , group 2 (Futurabond NR+Grandio), group 3(All Bond SE+ Aelite LS Posterior), group 4 (LS System Adhesive Primer & Bond+Filtek P90). All the specimens were thermocycled for 2000 cycles (5-50oC). In each group, half of the specimens (n=12) were subjected to 200,000 cycles of loading at 80 N. Epoxy resin replicas of 32 specimens (4 restorations in each subgroup) were evaluated using SEM and the interfacial gaps were measured. Finally, the teeth were immersed in 0.5% basic fuchsin dye for 24 hours at 370C, then sectioned and observed under stereomicroscope. The data were analyzed using Kruskal-Wallis and Mann-Whitney U tests and the comparison between occlusal and gingival microleakage was made with Wilcoxon test. Results: Within unloaded or loaded specimens, there were no significant differences in microleakage among four groups on the occlusal margins (P>0.05). But there were statistically significant differences in microleakage between silorane and Aelite on the gingival margins (P<0.05). No statistically significant differences were found between the microleakage of the loaded and unloaded groups on both occlusal and gingival margins for all materials (P>0.05). Conclusion: Silorane did not perform better than the conventional low shrinkage methacrylate-based composite in terms of sealing ability (except Aelite). Cyclic loading did not increase the extent of leakage in any groups.